Childhood Vasculitis - An Update - Islam, Mohammad Imnul; Talukdar, Manik Kumar; Rahman, Shahana Akhter (Bangladesh Journal of Child Health, 2012)
DOI: http://dx.doi.org/10.3329/bjch.v36i1.13033 Bangladesh J Child Health 2012; Vol 36 (1): 30-35